Comparison of Lignin Degradation in Empty Oil Palm Bunches Biomass with Alkaline Pretreatment - Tayon, Felix; Maryana, Roni; Ariyanti, Dita; Garia, Ori Yansa (MUNISI: Military Mathematics and Natural Sciences, 2025)
Lignocellulose is an abundant polysaccharide component in nature and consists of cellulose, hemicellulose and lignin. Lignin degradation is a key step in the processing of lignocellulosic biomass from empty oil palm fruit bunches to produce bioenergy and valuable chemicals. Alkaline pretreatment method has become an effective approach in lignin degradation. This study aims to compare alkaline pretreatment with other methods in terms of lignin degradation efficiency. The initial treatment was carried out by cooking using a bench scale reactor at a temperature of 150 oC for 30 minutes. Characteristics before and after alkaline pretreatment were analyzed using Fourier Transform Infrared (FTIR). The research results showed the lowest lignin content was 7.71% with alkali pretreatment using a reactor.